Metabolomics Analyses Provide Insights Into Nutritional Value and Abiotic Stress Tolerance in Halophyte Halogeton glomeratus - Wang, Juncheng; Yang, Ke; Yao, Lirong; Ma, Zengke; Li, Chengdao; Si, Erjing; Li, Baochun; Meng, Yaxiong; Ma, Xiaole; Shang, Xunwu; Wang, Huajun (Frontiers in Plant Science, 2021)
Halogeton glomeratus is a succulent annual herbaceous halophyte belonging to the Chenopodiaceae family, has attracted wide attention as a promising candidate for phytoremediation and as an oilseed crop and noodle-improver. More importantly, H. glomeratus has important medicinal value in traditional Chinese medicine. However, there are few comprehensive studies on the nutrients, particularly secondary metabolites. Here, we adopted untargeted metabolomics to compare the differences in metabolites of different tissues (root, stem, leaf and seed) and identify the compounds related to pharmacological effects and response to abiotic stress in H. glomeratus. A total of 2,152 metabolites were identified, and the metabolic profiles of root, stem, leaf and seed samples were clearly separated. More than 50% of the metabolites showed significant differences among root, stem, leaf and seed. The KEGG pathway enrichment analysis of differential metabolites suggested an extensive alteration in the metabolome among the different organs. Furthermore, the identified metabolites related to pharmacological effects and response to abiotic stress included flavones, flavonols, flavandiols, glucosinolates, isoquinolines, pyridines, indoles, amino acids, lipids, carbohydrates and ATP-binding cassette transporters. These metabolites have application in treating human cardiovascular diseases, cancers, diabetes and heart disease, induce sleeping and have nutritive value. In plants, they are related to osmotic adjustment, alleviating cell damage, adjusting membrane lipid action and avoiding toxins. To the best of our knowledge, this is the first metabolomics-based report to overview the metabolite compounds in H. glomeratus and provide a reference for future development and utilization of H. glomeratus.